Removal efficiency of pesticide residues on pesticide-spiked Perilla Leaf and Broccoli surfaces using microplasma-treated water - Muhammad Saiful Islam Khan; Yun-Ji Kim; Jae-Hwan Ahn (PLoS ONE, 2026)
In the current study, we evaluated the applicability of a microplasma device to reduce pesticide residues from the surface of perilla leaf and broccoli. We compared the pesticide removal efficiencies of four different washing methods: soaking in water, bubbling water, microplasma- treated water, and chlorine water. Pesticide-spiked food produce surfaces were treated individually with 2 mL of 2000 ppm of the pesticide solutions diazinon and chlorpyrifos. Washing water treated with microplasma was applied in two different ways, i.e., in bubbling and aerosolized modes. The removal efficiency of pesticides from the produce surface was determined by HPLC analysis following 4 min of treatment. Washing with microplasma-treated water (both under water and aerosolized modes) and chlorine water removed 80.84–87.17% of pesticides from perilla leaves and 51.74–67.77% from broccoli, irrespective of pesticide type. Evaluation of the effective washing systems at different temperatures showed that reducing the temperature from 22°C to 10°C resulted in greater pesticide removal and/or degradation in the case of washing with microplasma-treated water; however, chlorine water washing showed a reverse trend. No significant color differences were observed for any of the washing treatments (p > 0.05), even after one week of refrigerated storage.